A uniform hydrogen degradation law for high strength steels. (May 2016) - Yu, Haiyang; Olsen, Jim Stian; Alvaro, Antonio; Olden, Vigdis; He, Jianying; Zhang, Zhiliang
Highlights: A specimen geometry independent hydrogen degradation law is proposed. The calibration procedure based on conventional tensile tests is established. Hydrogen informed cohesive zone modeling is performed in constant loading scenarios. The effects of strain rate and cold creep on the hydrogen degradation law are discussed. Abstract: The degrading effect of hydrogen on high strength steels is well recognized. The hydrogen degradation is dependent not only on hydrogen content, but also on geometric constraints or equivalently, level of stress triaxiality, which means the hydrogen degradation locus is not likely to be a unique material property. Experimental data on notched tensile tests reported by Wang et al. are analyzed via cohesive zone modeling, and a cohesive strength based uniform hydrogen degradation law is proposed upon normalization of hydrogen degradation loci with different specimen geometries. Since the effects of hydrogen content and geometric constraints are decoupled during normalization, the proposed law is applicable to all the specimen geometries as a material property. This law is subsequently applied to simulate the constant loading tests performed on the same material. Excellent agreement is observed between the simulation and test results in terms of incubation time for fracture initiation and highest permissible initial hydrogen content. The inconsistency observed in one of the cases is discussed, suggesting that the effects of strain rate and stress relaxation need to be taken into account in order to improve the transferability of the degradation law calibrated from tensile tests to constant loading situations.